Isolation and molecular characterization of potassium-solubilizing bacteria from limestone mountain of Bahorok, Langkat District, Indonesia - IMAM HARTONO BANGUN; HAMIDAH HANUM; TENGKU SABRINA (Society for Indonesian Biodiversity, 2023)
Abstract. Bangun IH, Hanum H, Sabrina T. 2023. Isolation and molecular characterization of potassium-solubilizing bacteria from limestone mountain of Bahorok, Langkat District, Indonesia. Biodiversitas 24: 4175-4184. In agricultural practices, ensuring an adequate supply of potassium to plants is crucial for optimal growth and productivity. However, the exchangeable K is tightly bound to soil minerals such as mica, feldspar, and clay minerals, making it unavailable for plant uptake. K-solubilizing bacteria K can dissolve potassium from the mineral layer and be available to plants. The Previous study has found 11 bacterial isolates capable of solubilizing K in Aleksandrov solid media. This study aimed to select the best K-solubilizing bacteria for solubilizing K in soil and to perform molecular identification of these bacteria. A novel finding from this study is that specific KSBs enhance the levels of exchangeable K in the soil through various mechanisms, as evidenced by increased exchangeable Ca, Mg, and soil pH. Additionally, the research identified two newly discovered bacterial species capable of potassium solubilization: Paraburkholderia phymatum and Burkholderia paludis. Furthermore, the study suggests the existence of an unknown mechanism for K solubilization, indicated by the observed increase in soil pH during the process.